The impact of a computerized physician order entry system implementation on 20 different criteria of medication documentation: a before-and-after study - Jungreithmayr, Viktoria; Meid, Andreas; Bittmann, Janina; Fabian, Markus; Klein, Ulrike; Kugler, Silvia; Löpprich, Martin; Reinhard, Oliver; Scholz, Lucienne; Zeeh, Birgit; Bitz, Wolfgang; Bugaj, Till Johannes; et al. (BMC medical informatics and decision making, 2021)
The medication process is complex and error-prone. To avoid medication errors, a medication order should fulfil certain criteria, such as good readability and comprehensiveness. In this context, a computerized physician order entry (CPOE) system can be helpful. This study aims to investigate the distinct effects on the quality of prescription documentation of a CPOE system implemented on general wards in a large tertiary care hospital.